Spatiotemporal characteristics of the pharyngeal teeth in interspecific distant hybrids of cyprinid fish: Phylogeny and expression of the initiation marker genes - Gu, Qianhong; Yuan, Hui; Zhong, Hui; Wei, Zehong; Shu, Yuqin; Wang, Jing; Ren, Li; Gong, Dingbin; Liu, Shaojun (Frontiers in Genetics, 2022)
As an important feeding organ and taxonomical characteristic, the pharyngeal teeth of cyprinid fish have very high morphological diversity and exhibit species-specific numbers and arrangements. Many genes have been verified to regulate the pharyngeal teeth development and act as the initiation marker for tooth. Six initiation marker genes for pharyngeal teeth were used as RNA probes to investigate expression pattern, and these genes were further used to construct phylogenetic tree for cyprinid fish included some distant hybrids. The results from in situ hybridization showed that similarities and differences existed in the expression of dlx2b, dlx4b, dlx5a, pitx2, fth1b and scpp5 in pharyngeal region of the hybrids (BT) by the crosses of blunt snout bream (BSB, ♀) × topmouth culter (TC, ♂). Particularly, we found a high specificity marker gene scpp5 for early development of pharyngeal teeth. Scpp5 expression pattern established a clear graphic representation on the spatiotemporal characteristics of the early morphogenesis of pharyngeal teeth in BT and BSB. Our results suggested that the scpp5 expression in 4V1, 3V1 and 5V1 in BT occurred earlier than that in BSB, while the replacement rate of pharyngeal teeth (4V2, 3V2 and 5V2) was faster in BSB. Phylogenetic analysis revealed that the six marker genes were highly conserved and could be used as the molecular marker for identifying the parents of the distant hybrids in cyprinid fish. The expression patterns of the scpp5 gene was examined in various tissues, including the brain, gill, heart, liver, muscle, skin, fins, gonad, eye and kidney, showing that the scpp5 gene was ubiquitously expressed, indicating its important role in cyprinid fish.